Generative AI and the Metaverse: A Scoping Review of Ethical and Legal Challenges - Aliya Tabassum; Ezieddin Elmahjub; Aasim I. Padela; Andrej Zwitter; Junaid Qadir (IEEE Open Journal of the Computer Society)
The metaverse, a pioneering digital realm merging virtual and augmented realities with Artificial Intelligence (AI), represents a transformative environment where digital and physical realities converge seamlessly. Generative AI (GenAI) is indispensable in powering the metaverse's dynamic and immersive experiences, enabling the autonomous generation of diverse digital content. Large Language Models (LLMs), as a component of GenAI, play a critical role by facilitating real-time communication, multilingual translation, and personalized interactions, enhancing user engagement in shared virtual spaces. This scoping review explores the interdependence between GenAI and the metaverse and the unique ethical and legal challenges that emerge from their integration. It identifies key ethical and legal issues, such as bias in AI-generated content, misinformation, and data privacy concerns, related to the deployment of GenAI and LLMs, and offers strategic recommendations for addressing these challenges responsibly. Emphasizing the transformative potential of these technologies, this review highlights the necessity of developing tailored ethical and legal frameworks to manage their convergence responsibly, ensuring equitable and sustainable growth within the metaverse.